Transformation of Sustainable Aquaculture Policy: The Blue Economy Perspective in Promoting Food Security - Noka Omalia; Nellis Mardhiah (Balai Besar Riset Sosial Eonomi Kelautan dan Perikanan, 2025)
The high potential of aquaculture does not automatically correlate with the achievement of sustainable food security due to the weak implementation of local aquaculture practices in the region. Therefore, this study aims to identify the potential of aquaculture, the challenges of local practices, and recommendations for blue economy-based aquaculture policy transformation in promoting food security in West Aceh Regency. Data collection was conducted using a qualitative approach with in-depth interviews, field observations, and documentation studies. Informants were selected using purposive sampling techniques involving policy actors and key stakeholders in the aquaculture sector, including local government (policy actors), academics and knowledge institutions, as key actors, and private parties involved in the production and distribution chain. Data analysis was carried out through data condensation, data reduction, data verification, and conclusion drawing. The results show that the increase in aquaculture potential in West Aceh Regency is not directly proportional to sustainability and food security due to the gap between production expansion and governance capacity. The main obstacles include low adoption of eco-friendly technologies, limited capacity of farmers, and weak waste management, which reflect the lack of integration of blue economy principles such as resource efficiency and zero waste. This study identifies strengthening governance, zero waste-based waste management, and multisectoral collaboration as key leverage points in sustainable aquaculture transformation. These findings indicate that strengthening aquaculture as a pillar of local food security requires policy leverage on governance reform, particularly zero waste management, capacity building and extension services for farmers, and cross-sector collaboration based on the blue economy.